Econometric Modeling of Electricity Consumption by Households as a Tool for the Calculation of Social Norms of Consumption - Zaytseva, Yulia Vladimirovna (Economy of Regions, 2016)
Since July 2016, in all regions of Russia, it is planned to introduce the electricity tariffs with the social norm of consumption. The calculation method of the social norms of consumption for the different types of households is approved by the Government decree of the Russian Federation. The resolutions of the decree regulate the volume of electricity supply within a social norm not less than 70 % of the real volume of the supply of electric energy to the population. In this article, the analysis of the validity of the methods for calculating the social norm on the basis of the statistical analysis of the data on electricity consumption by Russian households is made. The purpose of this work is to develop an econometric model of electricity consumption by Russian households and to calculate reasonable social norms for different categories of households on the basis of this model. As the explanatory variables, the factors describing the size and living conditions of households were selected: the number of residents, the presence or absence of electric stove, the type of settlement (city or village), the climatic conditions of the region. The simulation results showed that according to the requirements of the social norm (at least 70 percent of the actual volume of electric energy delivery), the norms for households consisting of one person should be from 110 to 210 kWh depending on the living conditions. The necessary increment of social norms for the second, third and subsequent members of the households of different categories are also identified. The received values of social norms are not quite consistent with the values regulated by the legislatively approved method. For some types of households, the values are underestimated. The developed model considers the regional specific features of electricity consumption and can be useful for the calculation of the social norms of electricity consumption in the regions of the Russian Federation.